Efektivitas Perpustakaan Konvensional Sebagai Sumber Belajar IPA Terhadap Era 5.0 di SMPN 1 Cluring - I Ketut Mahardika; Silvia Agustiyani; Rina Tut Jayati; Indri Wulandari; Firdha Yusmar; Rizka Elan Fadilah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The library is a supporting facility in the world of education that has various benefits, one of which is as an information center covering various sciences. In running a library there is a library effectiveness that can be supported by several factors. In the 5.0 era the effectiveness of conventional libraries has experienced a shift due to the existence of virtual libraries. The purpose of this study is to describe the effectiveness of conventional libraries in the 5.0 era by using a sample of SMPN 1 Cluring educational institutions. This study uses observation and interviews in collecting data and using descriptive qualitative methods in the preparation of articles. The data obtained indicate that the effectiveness of conventional libraries at SMPN 1 Clearing has decreased due to technological advances that create products that are more accessible. the industrial revolution 5.0 affects the effectiveness of conventional libraries as learning resources and information centers. This causes students to prefer to use virtual libraries because it is more practical and wider information can be obtained from various sources, so that the effectiveness of conventional libraries based on librarian activities decreases.